Neurolymphomatosis in Non-Hodgkin’s Lymphoma - Rozenkov , Serhii; Kirilyuk , Sophia; Negrich , Tetiana (The Ukrainian Scientific Medical Youth Journal, 2023)
non-Hodgkin’s lymphomas (NHLs) are a heterogeneous group of hematopoietic puffins, with diphun B-velicocyclotinous lymphoma accounting for 25% of all NHLs and having the greatest midline to axis growth (Leeuwenуе et al., 2014). Of all NHLs, the central and peripheral nervous systems are most often affected in diphytic B-lycocytic lymphoma (Padala, & Kallam, 2022. Liu, & Barta, 2019). In NHL, infiltration of cranial and peripheral nerves can be detected - neurolymphomatosis (NL) emerges. NL is a very rare condition and occurs in about 0.2% of patients with NHL (Baehring, Damek, Martin, Betensky & Hochberg, 2003). These infiltrations can manifest with detection of mononeuropathy, multiple neuropathy, symmetric neuropathy or plexopathy (Grisold W., Grisold A., Marosi, Meng, & Briani, 2015). The aim of the work was to study the features of the clinical course, diagnosis and treatment of neurolymphomatosis in the form of lesions of the trigeminal, facial cranial nerve and the left ulnar nerve in diffuse B-bollichelial non-Hodgkin lymphoma based on a clinical case. We present a review of a clinical case of peripheral nervous system involvement in a patient born in 1977 with diffuse B-cell non-Hodgkin’s lymphoma. The diagnosis was established on the basis of clinical manifestations of lesions of the branches of the trigeminal and left facial nerves, the left ulnar nerve, magnetic resonance imaging of the head and brain, electroneuromyography, and immunohistochemical examination of the infiltrate biopsy from the affected buccal branch of the left facial nerve. In March 2022, the patient developed moderate peripheral paresis of the mimic muscles on the left side, burning pain with impaired tactile and pain sensitivity of the dorsum, wing of the nose, and left instep. A week later there was a decrease in the strength, tactile and pain sensitivity, and patience of the fourth and fifth fingers of the left hand. Within a month, the burning pain had spread to the left cheek, periorbital, and chin areas of the face. In 2021, the patient was diagnosed with B-bollichelial non-Hodgkin’s lymphoma with involvement of the right axillary, supraclavicular lymph nodes, left breast, followed by chemotherapy and clinical remission. Magnetic resonance imaging of the head revealed a perineural lesion of the third branch of the right trigeminal nerve, the second branch of the left trigeminal nerve, and the cheek branch of the left facial nerve. Electroneuromyography revealed an axonal lesion of the left ulnar nerve. The results of examination of the infiltrate biopsy from the affected buccal branch of the facial nerve specimens confirmed non-Hodgkin’s diffuse B-cell lymphoma, GCB-phenotype and nerve damage due to NHL. Treatment of multiple neuropathy with glucocorticosteroids, nonsteroidal anti-inflammatory drugs, acelicholinesterase inhibitors, and specific chemotherapy resulted in limited therapeutic effect. Prescribing pregabalin resulted in decreased reduction of neuropathic facial pain. Thus, neurolymphomatosis is a rather rare manifestation of non-Hodgkin’s lymphomas, the use of magnetic resonance imaging of the head and brain as well as immunohistochemical examination of the affected nerve infiltrate biopsy is important to confirm the diagnosis. In the Ukrainian scientific medical literature, there are few descriptions of cases of neurolymphomatosis in NHL, although they occur in patients, and it is necessary to describe in more detail the peculiarities of the collicular course of the diagenesis and treatment in these cases.